Pengaruh Inokulasi Lactobacillus plantarum dan Saccharomyces cerevisiae terhadap Fermentasi dan Kecernaan In Vitro Silase Kulit Buah Kakao - Muhammad Askari Zakariah; Ristianto Utomo; Zaenal Bachruddin (Buletin Peternakan, 2016)
The objective of this study was to identify the effect of L. plantarum and S. cerevisiae mixed culture inoculation into cocoa pods silage on chemical composition and in vitro digestibility. The four treatments were: 1 kg freshly harvested cocoa pods without inoculants as control (K); K + L. plantarum (KLp); K + S. cerevisiae (KSc); and K + L. plantarum and S. cerevisiae mixture (KLp+Sc) 0.1% dry matter, Cassava meal were added in all treatments. Each treatment was replicated 3 times, and then fermented for 21 days. Parameters observed in current study were gas test production, ruminal fermentation parameter, and in vitro digestibility. The collected data were analyzed by one-way analysis of variance and followed by Duncan’s new Multiple Range Test for data with significant differences. Result showed that the mixed culture Lp+Sc inoculation increased (P<0.05) chemical quality of cocoa pods by reducing fibre fraction and increase NFE contents, increased degradation rate, degradation theory, reduced rumen pH, and propionate acid production, without affecting acetate to propionate ratio, microbial protein synthesis, and digestibility of cocoa pod silage.